IoT - Enabled Cashback - Based Recycling Management System - Abu Bakar, Aisyah; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2026)
The IoT-Enabled Cashback-Based Recycling Management System addresses inefficient recycling processes and low participation at Universiti Tun Hussein Onn Malaysia (UTHM). Integrating IoT technology with incentive mechanisms like cashback and deposit return schemes, the system encourages students and staff to recycle by offering financial rewards based on the volume of recyclables disposed of. Research highlights that reward, such as cashback or recognition, significantly enhance recycling behavior, making it a pivotal factor in the system’s success. The project combines IoT with behavioral science to track, reward, and provide data-driven insights into recycling activities. Personalized incentives and transparent feedback aim to foster a culture of sustainability on campus. This innovative approach is designed to improve recycling rates, minimize waste contamination, and enhance waste management efficiency at UTHM, contributing to broader environmental goals and promoting active engagement in sustainable practices.